A ReaxFF molecular dynamic study on pyrolysis behavior and sulfur transfer during pyrolysis of vulcanized natural rubber. (15th February 2022) - Wei, Xin; Yu, Jie; Du, Jiaxing; Sun, Lushi
Highlights: The pyrolysis behavior of different cross-linked natural rubber was studied. Three sulfur cross-linked models and a carbon cross-linked model were built. Sulfur cross-linked structures have the lower onset decomposition temperature. The transformation and distribution of sulfur were discussed. Abstract: In this work, ReaxFF molecular simulations were performed to study the pyrolysis behavior of chemical cross-linked natural rubber (NR) under non-isothermal and isothermal conditions. Three different sulfur vulcanized NR models were established and simulated to study the effect of inner sulfur structure on NR decomposition behavior and sulfur evolution in comparison with carbon cross-linked structure. To understand the NR decomposition with temperatures, the non-isothermal simulations were performed between 300 and 3800 K at a 50 K ps −1 heating rate. The results reveal that the decomposition process can be classified into four stages: 1) Structure adjustment; 2) Decomposition of the main carbon chains; 3) Secondary decomposition of heavy tar; and 4) Deep decomposition of light tar. Based on the results of non-isothermal pyrolysis, four different temperatures were selected for the isothermal simulations. Compared with carbon cross-linked NR, sulfur cross-linked structures facilitate the generation of C2 H4 and C4 H6 in the gas phase at low temperatures. At higher temperatures, more heavy tar is generated. Regarding the sulfur evolution, the sulfur-containing products mainly include H2 S, thiophene, sulfide, and thiol. The distribution of sulfur-containing products with temperatures follows the similar pattern with the product distribution of main compounds. At higher temperatures, most sulfur exists in the form of thiophene compounds. In particular, the structure with single CS cross-links facilitates the generation of H2 S at low temperatures. The results of this work provide insight into the sulfur transformation and pyrolysis behavior of vulcanized NR.